2001
DOI: 10.2337/diabetes.50.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Body Fat Distribution Induce Endothelial Dysfunction by Oxidative Stress

Abstract: Endothelial dysfunction has been reported in obese subjects, but its mechanism has not been elucidated. We have therefore investigated 1) the possible relationship among BMI, waist-to-hip ratio (WHR), and endothelium-dependent vasodilation and 2) whether oxidative stress participates in endothelial dysfunction. We recruited 76 healthy subjects (50 men and 26 women aged 21-45 years) and measured their BMI (kg/m 2 ), WHR, and insulin resistance (IR) estimated by the homeostasis model assessment (HOMA). Endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
237
3
14

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(280 citation statements)
references
References 29 publications
26
237
3
14
Order By: Relevance
“…There is no causal explanation for these associations; however, recent reports have indicated that obesity and abdominal fat distribution induce endothelial dysfunction by oxidative stress. 29 It has been recently accepted that the elevated level of hsCRP is a very strong predictor for CVD. 30 The lower the hsCRP, the lesser the risk for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…There is no causal explanation for these associations; however, recent reports have indicated that obesity and abdominal fat distribution induce endothelial dysfunction by oxidative stress. 29 It has been recently accepted that the elevated level of hsCRP is a very strong predictor for CVD. 30 The lower the hsCRP, the lesser the risk for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…86,87 Additionally, these cardiovascular risk factors are all associated with vascular endothelial dysfunction. 88 Indeed, studies in children and adults examining the association between obesity and endothelial dysfunction have identified insulin resistance, 34,35,89 glucose intolerance, 48,57 serum lipoprotein and apolipoprotein levels, 34,49 adipocytokines, 47 inflammation, 40,41 oxidative stress 90 and endothelial nitric oxide synthase 91 as possible pathophysiological intermediaries. Much recent research has focused on the role of adipocytokines and other obesity-related peptides as important molecules in the pathophysiological link between increased adiposity and cardiovascular disease.…”
Section: Mechanisms Linking Obesity and Atherosclerosismentioning
confidence: 99%
“…However, there are mixed reports on resistance vessel endothelial function in human obesity, demonstrating either impaired [Perticone et al, 2001] or normal endothelial function [Tack et al, 1998]. Vascular smooth muscle dysfunction has also been described in resistance vascular beds in obese subjects [Sivitz et al, 2007].…”
Section: Chapter VII Vascular Function In Obese and Lean Subjects Witmentioning
confidence: 99%